2007
DOI: 10.1068/p5690
|View full text |Cite
|
Sign up to set email alerts
|

Intrasensory Attention: Kinaesthetic versus Cutaneous Inputs

Abstract: Blindfolded participants felt pairs of raised-line drawings simultaneously, one with each index finger. The stimuli presented at each fingertip were 180 degrees rotations of each other (eg 6 and 9). One finger moved (either actively or passively), and this in turn caused movement of a matched raised line underneath the stationary finger on the other hand, in a yoked manner. Thus, a 6 at the moving finger would be felt as a 9 on the stationary finger. On all trials there was a raised line moving underneath the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
1
11
1
Order By: Relevance
“…1). Based on the findings of Symmons et al (2007), we hypothesized that cutaneous inputs alone (i.e., those from the stationary finger) would be weighted more heavily than kinesthetic inputs alone (i.e., those from the moving finger). As such, simply moving a raised-line stimulus under a stationary finger without kinesthetic information would be enough to result in a report of that angle in preference to the rotated version of the angle experienced at the moving fingertip when this finger was deprived of cutaneous input.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Based on the findings of Symmons et al (2007), we hypothesized that cutaneous inputs alone (i.e., those from the stationary finger) would be weighted more heavily than kinesthetic inputs alone (i.e., those from the moving finger). As such, simply moving a raised-line stimulus under a stationary finger without kinesthetic information would be enough to result in a report of that angle in preference to the rotated version of the angle experienced at the moving fingertip when this finger was deprived of cutaneous input.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study are four experiments that tested the idea that the effect observed by Symmons et al (2007) is an example of sensory integration in the form of capture and, specifically, tested whether cutaneous information can dominate kinesthesis. In Experiment 1, we explored whether the effect observed by Symmons et al (2007) occurs using stimuli simpler than letters and numbers (i.e., angles, which may make it easier to attend to movement than do complex shapes), and whether the removal of cutaneous stimuli (i.e., no raised-line or shear information) from one finger matters (i.e., when self-generated movement became the major cue for shape), a condition not present in Symmons et al's (2007) experiment. From the findings of Symmons et al (2007), we hypothesized that this would result in cutaneous capture of kinesthesis.…”
mentioning
confidence: 99%
See 3 more Smart Citations